An Economic Analysis of Mixing Wastes - Rob F.T. Aalbers; Herman R.J. Vollebergh (Tinbergen Institute, 2005)
Using a general equilibrium model with heterogeneous waste, this paper studies optimal waste policy when households have to exert separation effort to produce near-homogeneous waste streams suitable for recycling. Our model explicitly allows for changes in the composition (quality) of waste streams depending on how much effort households are willing to spend on separating different types of waste. Accordingly, we are able to generalize some earlier contributions to the waste management literature and demonstrate that with both mixing and effort included, a first-best optimum is feasible under reasonable conditions. In particular, we find that a (modified) deposit-refund system still provides the optimal incentives to guide recycling as well as legal disposal (landfilling) and illegal dumping. Both the number and level of taxes and subsidies needed to reach the first-best depend crucially on the socially optimal level of dumping as well as the socially optimal composition of the mix.
Keywords: H21; H23; Q53; 330; Economics of Waste; Recycling; Environmental Taxes and Subsidies; General Equilibrium Theory